(untitled) (Vietnam Journal of Community Medicine, 2026)
Surgical patients require adequate nutrition to reduce complications and promote wound healing; however, optimizing nutrition is a difficult issue both theoretically and practically. Objective: To evaluate the effectiveness of nutritional intervention using a commercially available formula for patients undergoing planned abdominal surgery. Methods: A randomized controlled trial was conducted in Thai Binh province from January 2023 to October 2024, involving 54 individuals in the intervention group supplemented with Leanmax formula (57g/serving mixed in 180ml water, twice daily for 2 months) and 54 individuals in the control group with a normal diet. Results: The intervention group showed several positive differences compared to the control group; statistically significant differences (p<0.05) were: shorter hospital stay (2.2 days less); frequent surgical site infections 16.7%; less frequent gastrointestinal infections (16.7%); less frequent use of additional antibiotics after surgery (16.7%); more than 3.0 kg of mean weight and more than 0.8 kg/m2 of BMI; less than 38.9% weight loss and less than 33.3% risk of malnutrition; less than 22.2% bloating; less than 25.9% loss of appetite; less than 29.6% difficulty sleeping/sleep disturbances; and less than 38.9% fatigue. Other differences that tended to be better but not statistically significant (p>0.05) were: less frequent respiratory infections (3.7%), less frequent urinary tract infections (5.6%), less frequent constipation (1.9%), less frequent nausea (9.3%), and less frequent itching (14.8%). Conclusion: Supplementing Leanmax formula for patients undergoing planned abdominal surgery reduces hospital stay, decreases infection rates, and improves nutrition, digestion, and overall health.